Implementation of Bamboozle Digital Media to Improve Communicative Character in Social Studies Learning at MTs Darul Ulum - Silvia Emil; Isak Maulidah; Linda Arum Sanjaya; Dany Miftah M. Nur (ARIMA : Jurnal Sosial Dan Humaniora, 2025)
This research aims to explore the implementation of Bamboozle digital media in improving students' communicative character in social studies learning at MTs Darul Ulum. The approach used in this research is qualitative with a case study method. Data was collected through observation, in-depth interviews, and documentation to gain an in-depth understanding of how the use of Bamboozle media can influence students' communicative abilities. The research subjects were class VII.B students who were selected based on initial observations regarding their interest and involvement in learning. The research results show that Bamboozle media can increase students' activeness, enthusiasm and courage in communicating and expressing opinions during social studies learning activities. Apart from that, Bamboozle provides an interactive and fun learning atmosphere, so that it can build students' communicative character effectively. This research recommends Bamboozle as an alternative learning media to form communicative character in social studies learning.